2017
DOI: 10.1200/jco.2016.68.2153
|View full text |Cite
|
Sign up to set email alerts
|

CpG Methylation Signature Predicts Recurrence in Early-Stage Hepatocellular Carcinoma: Results From a Multicenter Study

Abstract: Purpose Early-stage hepatocellular carcinoma (E-HCC) is being diagnosed increasingly, and in one half of diagnosed patients, recurrence will develop. Thus, it is urgent to identify recurrence-related markers. We investigated the effectiveness of CpG methylation in predicting recurrence for patients with E-HCCs. Patients and Methods In total, 576 patients with E-HCC from four independent centers were sorted by three phases. In the discovery phase, 66 tumor samples were analyzed using the Illumina Methylation 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 34 publications
2
117
0
Order By: Relevance
“…The candidate miRNAs were determined by a LASSO algorithm with penalty parameter tuning with 10-fold cross-validation and an SVM-Recursive Feature Elimination (RFE) algorithm (Qiu et al, 2017). In total, nine common candidate miRNAs were further selected for the training cohort.…”
Section: Selection Of Mirnas For the Training Cohortmentioning
confidence: 99%
“…The candidate miRNAs were determined by a LASSO algorithm with penalty parameter tuning with 10-fold cross-validation and an SVM-Recursive Feature Elimination (RFE) algorithm (Qiu et al, 2017). In total, nine common candidate miRNAs were further selected for the training cohort.…”
Section: Selection Of Mirnas For the Training Cohortmentioning
confidence: 99%
“…More recently, Qiu et al recently demonstrated that aberrant DNA methylation also might be used to distinguish the risk of recurrence among patients with resected, early stage HCC . Those authors analyzed 66 tumors samples with an Illumina Methylation 450‐k bead chip, from which they isolated 46 CpG sites that were associated with either a high or low risk of recurrence.…”
Section: Dna Methylation Signatures Of Recurrence and Prognosismentioning
confidence: 99%
“…More recently, Qiu et al recently demonstrated that aberrant DNA methylation also might be used to distinguish the risk of recurrence among patients with resected, early stage HCC. 80 Those authors analyzed 66 tumors samples with an Illumina Methylation 450-k bead chip, from which they isolated 46 CpG sites that were associated with either a high or low risk of recurrence. They narrowed this set to 3 CpG sites near 3 genes (SCAN domain-containing protein 3 [SCAND3], SH3-conaining GRB2-like protein-3 interacting protein 1 [SGIP1], and peptidase inhibitor 3 [PI3]), which were then used to create a risk score.…”
Section: Dna Methylation Signatures Of Recurrence and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…6 An effective two-category classification model was generated for predicting early HCC recurrence based on at least three CpG methylation sites; this model was developed through analysis of 450K methylation chip data from 576 publicly available samples. 7 Analysis of 450K chip data also led to the identification of DNA methylation sites in the genome of peripheral blood mononuclear cells and T cells that were associated with HCC progression. 8 Bisulfite sequencing analysis in the Huh2 HCC cell line showed an association between abnormal DNA methylation and abnormal DLL3 expression.…”
mentioning
confidence: 99%